The Effects of Altitude and Rearing Period on Some Characteristics of Honey Bee Queens, Apis Mellifera Caucasica Gorbachev, 1916 (Hymenoptera: Apidae)1 - Canverdi, Nazli Pinar; Ozmen Ozbakir, Gonca; Cankaya, Soner; Duman, Muzaffer; Kayaboynu, Umit; Yilmaz, Fatih; Gunbey, Belgin (Entomological Soc Turkey, Ege Univ, 2023)
In the study, some characteristics of honey bee queens, Apis mellifera caucasica Gorbachev, 1916 (Hymenoptera: Apidae), reared at two different altitudes (140 m vs 920 m) and three rearing seasons (May, June-I, June-II) in 2019-2020 were examined in Ordu. These are larvae grafting, length of the queen cell, weight of queens at various periods, and spermathecae parameters of queens. One-day old 50 larvae were grafted at each period and altitude. The effect of period and period*altitude interaction on the weight at emergence of queen was significant (p<0.001) while the effect of altitude and year was nonsignificant. Weights at emergence of queens were lower in May at high altitudes and in June-II at low altitudes. The effects of year, period and altitude were significant (p<0.001) in the terms of the diameter and volume of the spermathecae, and the number of spermatozoa in the spermathecae. When the two-year data was evaluated together, the number of spermatozoa in the spermathecae was higher in the queen bees reared in May. It is recommended to pay attention to the period and altitude when pollen and nectar flow is intense in queen rearing in Ordu and similar climatic conditions.
Özmen Özbakır, Gonca/0000-0003-1695-4012; Duman, Muzaffer/0000-0002-7600-6594; Yilmaz, Fati̇h/0000-0002-6069-7335
Keywords: Honeybee; Queen; Rearing Period; Spermathecae; Number of Spermatozoa